CHARACTERIZATION CHARCOAL FROM PALM KERNEL SHELLS BASED CHROMATOGRAPHY GC - MS AND DIFFRACTION X-RD - Nasution, Zainal Abidin; Nasution, Siti Salamah (IJRDO-Journal of Applied Science, 2016)
In 2015, the land area of oil palm plantations in Indonesia has reached10,701,436 Ha, with details of oil palm plantations owned by the people is 4,810,271 Ha, oilpalm plantations belonging to state-owned enterprises is 704,094 Ha and oil palm plantationsbelonging to private company is 5,207,071 Ha. Based one ton of fresh palm fruit bunches ofoil palm will produce 20 % - 23 % of CPO ; 5 % - 7 % PKO and the rest of the solid wastefrom process that is 20 % - 23 % of oil palm empty fruit bunches; 10 % - 12 % of oil palmfruit fiber and 7 % - 9 % palm kernel shells. Palm kernel shells is are formed from biomassof photo synthetic clorophyl leaves, working as a solar cell that absorbs the energy ofsunlight, and the converting carbon dioxide and water into a material containing carbon,hydrogen and oxygen. The material in solid form and if converted can be charcoal of palmkernel shells. Implementation of this study, oil palm shell charcoal is made by roastingtreatment of palm kernel shells. Roasting was treated of palm kernel shells obtained averageyield was 38.20 % (final roasting temperature of 348 0 C, at the time of palm kernel shells arebeing roasted no longer smoke).From the analysis of chromatograms GC - MS palm shell charcoal derived organiccompounds with dominant composition is Cyclopropyl with a concentration of 14.87 %;Acetic acid with a concentration of 17.01 % ; Benzenesulfonic acid with a concentration of12.11 % ; Benzene with a concentration of 7.30 % ; Phenol with a concentration of 15.59 %.Determination of oil palm shell charcoal with roasting and from testing XRD results that thequantity of the carbon content of the crystals was 12.28 % and the rest is amorphous carboncontent of 87.72%. Amorph carbon is not a solid form that dominates the oil palm shellcharcoal. So it becomes a nature as raw material for making oil palm kernel shells charcoalwith treatment roasting be the substitution of carbon black.